PENGARUH BUDAYA ORGANISASI, KOMITMEN ORGANISASI DAN RETALIASI TERHADAP INTENSI WHISTLEBLOWING - Sita Aulia; Dona Primasari; Syaiful Azhar (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2019)
The title of this research is “The effect of Organizational Culture, Organizational Commitment, and Retaliation toward Intention Whistleblowing”. The purpose of this study to determine the effect of organizational culture, organizational commitment and retaliation toward intention whistleblowing. This research uses purposive sampling technique, which is determine samples with particular criteria. The sample in this study is civil servants in KPP Pratama Purwokerto. Samples obtained as many as 78 respondents. Data collection techniques used survey techniques by distributing questionnaires as the research instruments. Data analysis techniques in this study used multiple linear regression analysis assisted by SPSS software. The results showed that organizational culture and organizational commitment have positive influence to intention whistleblowing. Retaliation have negative influence to intention whistleblowing. The results of this study are expected contribute in effort to enhance intention whistleblowing for civil servants in KPP Pratama Purwokerto by knowing the factors that can affect tendency of civil servants to report fraud.